Assessing the Potentiality of Using CXCL9 as A Predictive Biomarker for Acute and Chronic Toxoplasmosis, and Study the Correlation Between CXCL9, Toxoplasmosis and Thyroid Disorder in These Cases - Najeeb, Mariam Ali; Al-Qaisi, Amjed Qays Ibrahim (Iraqi Journal of Science, 2023)
Background: Chemokine (C-X-C motif) ligand (CXCL9) has an important role recruiting the T-lymphocytes and immune response after infection by inducing T-cells accumulation around the areas associated with infections. However, this role is poorly known in relation with Toxoplasma gondii infection and also in association with thyroid hormones, which the present study is focused on. Methods: Eighty-seven women were included in this study for the period between September 2021 and February 2022. Blood samples of uninfected healthy pregnant, in addition to aborted and pregnant women infected with toxoplasmosis, were collected. Sera were then obtained and stored at -10°C. Toxo-latex agglutination test was done, followed by detection of IgM and IgG antibodies, which were identified in sera of cases and controls using a commercially available enzyme-linked immunoassay. Finally, an ELISA test for CXCL9 and thyroid hormones tests were performed as well. Results: CXCL9 levels showed a non-significant increase in comparison with the control group. This increase was observed during the first 5 months of abortion and pregnancy. Thyroid hormones T3 and TSH were significantly higher in the aborted and pregnant women than the control group. Whereas T4 results revealed lower levels in the same group in comparison to the control group, specifically during the first 5 months of abortion and pregnancy for most of the groups. Conclusion: Determining CXCL9 chemokine levels in female patients infected with Toxoplasma gondii might play an important role in early diagnosis of Toxoplasmosis, especially during the first 5 months of abortion or pregnancy as well as thyroid hormones levels can be influenced or affected by the parasite infection, which can provide an indicator of thyroid dysfunction in general.